Urinary profiling of cis-diol-containing metabolites in rats with bisphenol A exposure by liquid chromatography-mass spectrometry and isotope labeling. Issue 3 (7th January 2016) - Li, Shangfu; Jin, Yibao; Wang, Jue; Tang, Zhi; Xu, Shunqing; Wang, Tiejie; Cai, Zongwei
Abstract : A rapid UPLC-MS method combined with isotope labeling technology was developed for the detection of cis-diol metabolites in rat urine after bisphenol A exposure. Abstract : Exposure to bisphenol A (BPA), an environmental contaminant, has been linked to metabolic disorders. However, there are no reports describing the effects of BPA on the profiling of cis-diol metabolites. It is challenge to detect these metabolites in biological samples because of their low abundance, high polarity and serious matrix interference. In this study, a chemical isotope-labeling method was applied to solve these problems. Acetone and deuterated acetone (acetone-d6 ) were used as chemical tags to label the rat urine samples, respectively. The light and heavy labeling products were recognized using the ShiftedIonsFinder software. The selected cis-diol metabolite signals were used to build a data set. The data set was applied to evaluate the changes in the urinary profiling of cis-diol -containing metabolites in rats with BPA exposure. The results showed that chromatographic separation and mass spectrometry detection of cis-diol metabolites were improved after acetone labeling. Using this method, the cis-diol metabolites were recognized easily from the urine samples. By comparing different dose administration on rats, the influence of BPA exposure on cis-diol metabolites was investigated. The analytes showing noticeable differences were identified. It was found that high-dose BPA exposure had strong effects on the cis-diol compound metabolism. The influences were mostly related to the metabolism of galactose and nucleoside and its analogues. The disturbance of the galactose metabolism by BPA is reported for the first time, to the best of our knowledge. This may have some implications for exploring the toxic effects of BPA exposure.